Paisajes culturales en circuito turístico: articulación y desarrollo de escenarios urbanos en Nátaga, Huila. (2023)
The municipality of Nátaga has consolidated dynamics and activities economic based on its territory that work alongside its natural, cultural, religious attractions, and its agricultural and livestock productions; Despite the above, they have not been efficiently linked to the tourist power that is born as an opportunity given the resources and inputs that this place has, for greater visibility of its qualities and productive characteristics. Therefore, the objective of this research is to identify and qualify all the values that could benefit the municipality in the potentiation of tourism dynamics from a recognition of territorial memory followed by a verification of information that serves to understand how these can benefit in the search for a common good understanding the space in which these activities are carried out, which in the investigation of solutions can serve as tools for the development of strategies, and are currently executed in rural areas and the urban area in the municipality of Nátaga, supported by bibliographic background and development plans that serve as support for the elaboration of diagnoses and alternatives to develop.